Aetiology, microbiology and therapy of periapical lesions around oral implants: a retrospective analysis. (27th December 2012) - Lefever, David; Van, Nele; Temmerman, Andy; Teughels, Wim; Quirynen, Marc
Abstract Objective The aim of this study was: (i) to evaluate whether an endodontic pathology on the extracted tooth or adjacent teeth of an implant site has an influence on the emergence of a periapical lesion, (ii) to retrospectively analyse the outcome of different treatment strategies, (iii) to determine which bacteria were present in periapical lesions. Methods The endodontic status of the tooth at the implant site and the adjacent teeth was explored and linked to the periapical status of the implant. For all the lesions treated since 2000, their survival was assessed. Finally, microbial samples (culturing) from the periapical lesions, were analysed. Results If an endodontic treatment or a periapical lesion at the apex of a tooth is present, a periapical lesion around the implant can be detected in 8.2% up to 13.6% (OR 7.2). For periapical pathology at the adjacent teeth, the percentage rises to 25% (OR 8.0). The best treatment option could not be found. Bacteria were found in 9/21 lesions. The most prominent species was P. gingivalis. Conclusions When an endodontic pathology is present on the extracted or neighbouring teeth, it is significantly more likely that a periapical lesion will develop around a future implant.